Hunger for iron: the alternative siderophore iron scavenging systems in highly virulent Yersinia - Rakin, Alexander; Schneider, Lukas; Podladchikova, Olga (Frontiers in Cellular and Infection Microbiology, 2012)
Low molecular weight siderophores are used by many living organisms to scavenge scarcely available ferric iron. Presence of at least a single siderophore-based iron acquisition system is usually acknowledged as a virulence-associated trait and a prerequisite to become an efficient and successful pathogen. Currently it is assumed that yersiniabactin (Ybt) is the solely functional endogenous siderophore iron uptake system in highly virulent Yersinia (Yersinia pestis, Y. pseudotuberculosis and Y. enterocolitica biotype 1B). Genes responsible for biosynthesis, transport and regulation of the yersiniabactin (ybt) production are clustered on a mobile genetic element, the High Pathogenicity Island (HPI) that is responsible for broad dissemination of the ybt genes in Enterobacteriaceae. However, the ybt gene cluster is absent from nearly half of Y. pseudotuberculosis O3 isolates and epidemic Y. pseudotuberculosis O1 isolates responsible for the Far East Scarlet-like Fever. Several potential siderophore-mediated iron uptake gene clusters are documented in Yersinia genomes, however neither of them have been proven to be functional. It has been suggested that at least two siderophores alternative to Ybt may operate in the highly virulent Yersinia pestis / Y. pseudotuberculosis group, and are referred to as pseudochelin (Pch) and yersiniachelin (Ych). Furthermore, most sporadic Y. pseudotuberculosis O1 strains possess gene clusters encoding all three iron scavenging systems. Thus, the Ybt system appears not to be the sole endogenous siderophore iron uptake system in the highly virulent yersiniae and may be efficiently substituted and / or supplemented by alternative iron scavenging systems.